REKOMENDASI PENGUBAHSUAIAN GEDUNG F POLITEKNIK NEGERI PADANG MENJADI BANGUNAN GEDUNG HIJAU - Partawijaya, Yan; Hamid, Desmon; Guspari, Oni; Aktorina, Wahyu; Yasrul, Latifah (Pusat Penelitian dan pengabdian kepada Masyarakat (P3M) Politeknik Negeri Padang, 2024)
Padang State Polytechnic (PNP), one of the first 17 polytechnics in Indonesia, is committed to creating a comfortable academic environment with adequate facilities and harmonious interaction between lecturers, staff, and students. Collaboration with many companies has increased the number of students and study programs admitted each year. However, the construction of facilities and infrastructure has reduced green open space by 26.88%. The construction of Buildings AB and E in 2012 has impacted the comfort and health of Building F users, obstructing air circulation and natural lighting, and increasing the demand for water and waste management. Recommendations are needed to convert Building F into a green building according to the Minister of Public Works and Housing Regulation No. 21 of 2021 to optimize natural resources, reduce environmental impact, and enhance comfort. This research aims to develop retrofit recommendations, including replacing window openings, adding green areas, planning natural lighting, and improving waste and wastewater management systems. Data was collected through literature review, observation, quantitative methods, interviews, and documentation. The initial assessment of Building F scored 21.81% according to the Checklist for Existing Buildings in the Green Building Performance Assessment, indicating a significant need for improvement. The implementation of the recommendations will potentially increase Building F's score to 70.30%, placing it in the